Enhancing the patient involvement in outcomes: a study protocol of personalised outcome measurement in the treatment of substance misuse - Alves, P. C. G. (2014)
Background: Involving patients in treatment is becoming increasingly popular in mental health [Sales & Alves: Personalized evaluation of psychological treatments: A review of tools and research designs, submitted]. However, in substance misuse treatment settings, the patient perspective about treatment tends to be overlooked. This has been cited as a key priority by Orford et al. [Addiction, 103: 875-885, 2008] who included patient feedback about treatment as one of ten areas requiring an urgent paradigm shift in addiction research and practice. This project will apply an innovative method to involve substance misuse patients in psychological therapies, by asking them to suggest topics to evaluate their treatment. These topics suggested by patients can be written as a list of personalised items, so-called as patient-generated outcome measures (PGOM). Despite its patient-friendly features, PGOM’s have never been used in this population, which is what this project aims to overcome. Methods/design: This project is part of an International Exchange Platform on Personalising Addiction Treatment. Data will be collected in two phases (pre-post study and focus groups with patients) to explore the following: 1). How reliable and sensitive to change are PGOM’s and standardised measures in substance misuse treatment? 2). Do PGOM’s add relevant information to standardised measures? 3). What are the views of substance misuse patients about personalised outcome assessment? 4). Development of guidelines on using PGOM’s in this population Discussion: This research will potentially demonstrate the diversity of personal problems among patients seeking substance misuse treatment, suggesting the relevance of PGOM as a method to personalise outcome measurement and, ultimately, guiding treatment provision. It is expected that, as in previous studies, PGOM’s will be perceived as helpful and patient-friendly tools, where patients may express their own concerns in a semi-structured setting. Similarly to other populations, we also expect PGOM’s to be reliable, valid and sensitive to clinical changes in substance misuse treatment, as well as more content informative than their standardised counterparts. If these results are achieved, we might hypothesize that PGOM’s are a potentially valid supplement to traditional standardised scales, by providing a closer insight to what motivates patients to participate in substance misuse treatment programmes.